Kemampuan Literasi Numerasi dalam Menyelesaikan Soal Asesmen Kompetensi Minimum Materi Statistika Ditinjau dari Adversity Quotient - Sri Hardini Nurul Wijayanti; Ira Kurniawati; Henny Ekana Chrisnawati (Program Studi Pendidikan Matematika FIP UNHASY, 2025)
Numeracy literacy is an ability that students must have to face the challenges of 21st century education. Adversity Quotient (AQ) or fighting power is one of the factors that influence this ability. This study aims to describe the numeracy literacy skills of high school students in solving Minimum Competency Assessment (AKM) type questions on statistics material in terms of Adversity Quotient of climber, camper, and quitter types. This research included descriptive qualitative research with research subjects as many as 6 students. The subjects in this study were determined by purposive sampling. The data taken are data on students' numeracy literacy skills obtained from the results of written tests and semi-structured interviews and students' AQ data obtained from the results of the AQ questionnaire. The validity of the data used is method triangulation. Data analysis techniques in this study include data reduction, data presentation, and conclusion drawing. The results showed that students with different AQ have different numeracy literacy skills. AQ climber students were able to achieve all indicators, namely solving practical problems using numbers and mathematical symbols, analyzing data from graphs, tables, charts, diagrams, and others, and interpreting the results of the analysis for decision making. AQ camper students were only able to achieve one indicator which is solving practical problems using mathematical numbers and symbols. Students with quitter type AQ were not able to achieve all indicators. The results of this study are expected to be used as input in designing learning strategies and assignments in mathematics subjects that are related to everyday life so as to improve students' numeracy literacy skills.